2020
DOI: 10.1017/s1754470x20000045
|View full text |Cite
|
Sign up to set email alerts
|

What are the recovery and attrition outcomes for group CBT and individual CBT for generalised anxiety disorder in an IAPT service? An exploratory study

Abstract: Group cognitive behavioural therapy (gCBT) is commonly used in Increasing Access to Psychological Therapies (IAPT) services. However, there is limited knowledge of the efficacy of gCBT as a delivery format for generalised anxiety disorder (GAD). To address gaps in literature, this study aims to explore the efficacy and attrition of individual and group CBT interventions, respectively, at Step 3 for GAD using data from a routine IAPT service over a 24-month period. Data were retrospectively derived from a routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…As a result, close examination of complex patterns and relationships between various factors can be explored. Considering attrition rates of around 30% for group interventions (based on CBT principles) (Fanous and Daniels, 2020), the study aimed to collect data from at least 15-20 participants during each phase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, close examination of complex patterns and relationships between various factors can be explored. Considering attrition rates of around 30% for group interventions (based on CBT principles) (Fanous and Daniels, 2020), the study aimed to collect data from at least 15-20 participants during each phase.…”
Section: Methodsmentioning
confidence: 99%
“…The increased need for cost-effective and efficient programmes has made way for the considerations of group interventions as part of the IAPT service. As a result, it has been proposed that group CBT has the potential to be more cost-effective than individual CBT while equality efficacious (Fanous and Daniels, 2020). The current overall retention rate (88%) reported across both phases adds to the current literature suggesting faith-based interventions have the capacity to improve acceptability and increase treatment retention (Adewoye, 2016;Anderson et al, 2015;Ramos et al, 2014).…”
Section: Recruitment and Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, enhancing high-quality support between therapy sessions is a key objective for improving CBT treatment outcomes (Lebeau et al, 2013). This is particularly critical in group therapy settings, where dropouts are higher and recovery rates are lower than in individual therapy settings (Fanous & Daniels, 2020;Fernandez et al, 2015;Hans & Hiller, 2013). Traditionally, therapeutic materials and exercises in CBT have been distributed as worksheets in pen and paper format or downloadable PDF format, requiring the patient to engage with these materials without any supervision.…”
Section: Introductionmentioning
confidence: 99%
“…Although in many cases professionals choose to treat these patients via individual interventions, especially when mood disorders are also involved, group therapy offers a number of potential benefits, especially in the context of primary care.A number of studies have found that group interventions can be just as effective as individual treatment (i.e. Fanous & Daniels, 2020) and that both approaches can be valid ways to treat anxiety disorders (Fawcett et al, 2020). Additionally, group CBT offers some advantages in terms of treatment efficiency which is always an important concern for public health services.…”
Section: Introductionmentioning
confidence: 99%